Toxicity studies of Sapindus laurifolius methanolic leaf extract in Wistar rats (Journal of Laboratory Animal Science, 2024)
Studies were aimed to evaluate the phytochemical composition of the Sapindus laurifolius leaves and toxicological  effect of the Sapindus laurifolius leaf extract using Wistar albino rats as a model animal. The phytochemical analysis  was performed using High Performance Thin Layer Chromatography (HPTLC). In toxicity studies, the acute oral toxicity  study was conducted as per the guidelines of Organization for Economic Co-operation and Development (OECD 423  Acute Toxic Class Method) for testing of chemicals. In repeated dose 28-day oral toxicity study (OECD 407), leaf extract  administered at the dose of 50, 200 and 800 mg/kg and limit dose of 1000 mg/kg. The phytochemical analysis revealed  the presence of saponins, flavanoids, glycosides and bitter principles. In acute toxicity study, the LD50 cut-off values  were found to be more than 2g/kg in leaf extract. In repeated dose 28-day oral toxicity, significant (P
Keywords: Sapindus laurifolius; phytochemical analysis; saponins; hepatotoxicity; nephrotoxicity